Assessing the quality, readability and reliability of online information on COVID-19 (Research, Society and Development, 2020)
During a public health crisis, the dissemination of reliable information, advice and experts’ opinions is essential for improving public comprehension of potential or actual health threats and enables the public to take informed decisions about risk mitigation measures. This study aimed to assess the quality, reliability and readability of internet-based information on COVID-19 available on Brazil’ most used search engines. A total of 68 websites were selected through Google, Bing, and Yahoo. The websites content quality and reliability were evaluated using the DISCERN questionnaire, the Journal of American Medical Association (JAMA) criteria, and the presence of the Health on Net (HON) certification. Readability was assessed by the Flesch Reading Ease adapted to Brazilian Portuguese (FRE-BP). The web contents were considered moderate to low quality according to DISCERN and JAMA mean scores. Most of the sample presented very difficult reading levels and only 7.4% displayed HON certification. Websites of Governmental and health-related authorship nature showed lower JAMA mean scores and quality and readability measures did not correlate to the webpages content type. COVID-19 related contents available online were considered of low to moderate quality and not accessible to general population. These findings indicate the need for further efforts on improving the quality of health-related content on internet, especially during public health emergencies.